Acute organic brain syndrome due to drug-induced eosinophilia. - Ng, S.C.; Lee, M.K.; Teh, A. (1989)
A 72 year old man developed acute organic brain syndrome associated with marked eosinophilia following self medication with a variety of drugs. Investigations revealed no other known causes of eosinophilia. Withdrawal of drugs resulted in dramatic drop in eosinophil count paralleled by clinical resolution of neurological problems. To our knowledge drug-induced eosinophilia has not previously been associated with acute organic brain syndrome.